PENGATURAN CYBER BULLYING DALAM UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Dewi Satyawati, I G A Ayu; Putri M. E Purwani, Sagung (Kertha Wicara : Journal Ilmu Hukum; Vol. 03, No. 02, Mei 2014, 2014)
The development of people’s needs in science and technology especially computer and internet has a very important role, either in the positive side or in the negative side. The most disturbing cyber crime which is still developing rapidly is the crime that related to the privacy of a human being, called cyber bullying. The issues that are being raised are the definition of cyber bullying and the types of cyber bullying. The purpose of this paper to understand cyber bullying and other types of cyber bullying. The paper uses the normative research methods, due to the vacancy norm against cyber bullying in the Act Number 11 of 2008 on Information and Electronic Transaction. This types of cyber bullying consists of flamming action, harassment, impersonation, outing (spreading other people's secrets), trickery, exclusion, cyberstalking, but in the Act Number 11 of 2008 on Information and Electronic Transaction only regulates the act of threatening and humiliation, while the act of cyber bullying hasn’t been clearly codified. So that the necessary arrangements are clearly against the rules of cyber bullying legislation in Indonesia
Keywords: cyber crime, cyber bullying, Act Number 11 of 2008 on Information and Electronic Transaction